2022
DOI: 10.1002/tox.23450
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses cell proliferation and triggers apoptosis in vemurafenib‐resistant melanoma cells by downregulating the EGFR signaling pathway

Abstract: Melanoma is a malignant tumor with aggressive behavior. Vemurafenib, a BRAF inhibitor, is clinically used in melanoma, but resistance to melanoma cytotoxic therapies is associated with BRAF mutations. Curcumin can effectively inhibit numerous types of cancers. However, there are no reports regarding the correlation between curcumin and vemurafenib-resistant melanoma cells. In this study, vemurafenibresistant A375.S2 (A375.S2/VR) cells were established, and the functional mechanism of the epidermal growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Curcumin exerts its anticancer property by inhibiting proliferation, EGFR phosphorylation, and promoting the degradation of EGFR by ubiquitination and apoptosis [ 129 ]. It has also been confirmed that the induction of apoptosis is mediated through the EGFR signaling pathway [ 130 ]. A study has shown that curcumin could control EGFR and EGFR downstream signaling molecules containing Akt, STAT3, and ERK1/2 [ 131 ]; curcumin inhibited EGFR via efficiently modulating gefitinib-insensitive EGFR degradation [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin exerts its anticancer property by inhibiting proliferation, EGFR phosphorylation, and promoting the degradation of EGFR by ubiquitination and apoptosis [ 129 ]. It has also been confirmed that the induction of apoptosis is mediated through the EGFR signaling pathway [ 130 ]. A study has shown that curcumin could control EGFR and EGFR downstream signaling molecules containing Akt, STAT3, and ERK1/2 [ 131 ]; curcumin inhibited EGFR via efficiently modulating gefitinib-insensitive EGFR degradation [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several concepts have been proposed to illustrate the pharmacokinetics alteration of bioactive compounds when co-treated with other active drugs, indicated the potential interaction occurred in organs and thus might alter distribution of phenolic compounds that were treated with drugs. 29 Result from drug-drug interaction test showed that premixed reaction did not alter their bioactivity suggesting the otoprotective role of FA. Those data indicated the relevance of pretreatment of transgenic zebrafish with FA to protect against the ototoxic effects of neomycin and allowed us to employee the pre/co-treatment method for the subsequent examinations with FA.…”
Section: Discussionmentioning
confidence: 98%
“…47 It was worth noting that curcumin, as a pigment extracted from ginger plant curcuma, had excellent antioxidant function. [48][49][50][51][52] Studies had shown that curcumin could prevent palmitic acid-induced decline in the survival rate of Saos-2 cells and reduce the production of ROS. 53 Curcumin could reduce the accumulation of ROS in HTR8/ Sveo cells caused by H 2 O 2 , thereby protecting HTR8/Sveo cells from damage induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the model of ketamine‐induced schizophrenia, the activities of antioxidant enzymes such as CAT and SOD were decreased in rat brain 47 . It was worth noting that curcumin, as a pigment extracted from ginger plant curcuma, had excellent antioxidant function 48–52 . Studies had shown that curcumin could prevent palmitic acid‐induced decline in the survival rate of Saos‐2 cells and reduce the production of ROS 53 .…”
Section: Discussionmentioning
confidence: 99%